St. Bonaventure on the Intellect: Sources and Teaching. - Vater, Carl A. (Review of Metaphysics, 2025)
The article focuses on St. Bonaventure's exploration of the concepts of the agent intellect and the possible intellect, which are central to understanding human cognition. St. Bonaventure engages with various interpretations of these concepts, particularly in the context of Aristotelian philosophy, and identifies eight distinct ways to understand their relationship. He ultimately rejects the notion that the agent intellect is a separate substance, arguing instead that both intellects are integral to the human soul and work together in the process of knowledge formation. The article highlights St. Bonaventure's commitment to the reality of human intellectual powers and the complexity of the cognitive process, emphasizing the interplay between divine illumination and human agency in acquiring knowledge.